Analisis Pilar Pembangunan Pariwisata Berkelanjutan di Taman Nasional Ujung Kulon, Indonesia - Elizabet Sagala, Afrilia (Politeknik Pariwisata Medan, 2023)
Sustainable or sustainable-based tourism has become the main focus of tourism development in Indonesia. The government and various stakeholders are involved in efforts to conserve nature, wise destination management, and empower local communities. One of the tourism destinations in Indonesia that carries a sustainable concept is a national park, one of the national parks in Indonesia that has an attraction for tourists is Ujung Kulon National Park. Ujung Kulon National Park is working with the Indonesian Rhinoceros Foundation (YABI) and the International Rhino Foundation in conserving the Javan rhino population by planning the construction of the Javan Rhino Study and Conservation Area (JRSCA). Based on this, efforts to protect the natural environment and biodiversity can be supported by designing the development of Ujung Kulon National Park as a tourist object by applying a sustainable approach. This research is a qualitative descriptive one that describes, describes, and describes the object under study (Arikunto, 2006). Research data obtained through primary and secondary data. Data analysis used is qualitative data analysis and SWOT analysis. The results of the linkage analysis of the 4 pillars of tourism development namely Destinations, marketing, industry and institutions, the industrial pillars have not supported optimally because they are only supported by homestays from people who lack knowledge in service and waste management. The recommendations from SWOT are developing sustainable and community-based tour packages to attract tourists who care about the environment, developing a planned visit management program by dividing tourist zones and limiting access to sensitive areas. Sustainable or sustainable-based tourism has become the main focus of tourism development in Indonesia, to measure the development of Ujung Kulon National Park is in accordance with the sustainable concept.